Determinants and outcomes of preterm births in Nigerian tertiary facilities. (2024)
Objective: To describe the incidence, and sociodemographic and clinical factors associated with preterm birth and perinatal mortality in Nigeria. Design: Secondary analysis of data collected through the Maternal Perinatal Database for Quality, Equity and Dignity (MPD-4-QED) Programme. Setting: Data from births in 54 referral-level hospitals across Nigeria between 1 September 2019 and 31 August 2020. Population: A total of 69 698 births. Methods: Multilevel modelling was used to determine the factors associated with preterm birth and perinatal mortality. Outcome measures: Preterm birth and preterm perinatal mortality. Results: Of 62 383 live births, 9547 were preterm (153 per 1000 live births). Maternal age (<20 years – adjusted odds ratio [aOR] 1.52, 95% CI 1.36–1.71; >35 years – aOR 1.23, 95% CI 1.16–1.30), no formal education (aOR 1.68, 95% CI 1.54–1.84), partner not gainfully employed (aOR 1.94, 95% CI 1.61–2.34) and no antenatal care (aOR 2.62, 95% CI 2.42–2.84) were associated with preterm births. Early neonatal mortality for preterm neonates was 47.2 per 1000 preterm live births (451/9547). Father's occupation (manual labour aOR 1.52, 95% CI 1.20–1.93), hypertensive disorders of pregnancy (aOR 1.37, 95% CI 1.02–1.83), no antenatal care (aOR 2.74, 95% CI 2.04–3.67), earlier gestation (28 to <32 weeks – aOR 2.94, 95% CI 2.15–4.10; 32 to <34 weeks – aOR 1.80, 95% CI 1.3–2.44) and birthweight <1000 g (aOR 21.35, 95% CI 12.54–36.33) were associated with preterm perinatal mortality. Conclusions: Preterm birth and perinatal mortality in Nigeria are high. Efforts should be made to enhance access to quality health care during pregnancy, delivery and the neonatal period, and improve the parental socio-economic status.